x - 6x = 0-5x= 0x = 0/-5which equals x = 0
Simply put, No.
It equals 0
The derivative of x is not x. X is the same as x^1, so you use the power rule which decreases the power by one and brings the exponent down, giving 1x^0, which is equal to 1.
anything x 0 = 0
x = 0
x is equals to 0 or 1. How is it solved? .... x.x =x x.x - x = 0 which can be solved by the usual formula for quadratic equations, or.. x.(x-1)=0 x= 0 or x-1 =0 x=0 or x=1
30 x 0
x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0
No because in this equation x = -6 -6--6 = 0